Microcavity quantum-dot systems for non-equilibrium Bose-Einstein condensation - EASTHAM, PAUL (My University, 2010)
We review the practical conditions required to achieve a non-equilibrium BEC driven by quantum dynamics in a system comprising a microcavity field mode and a distribution of localised two-level systems driven to a step-like population inversion profile. A candidate system based on eight 3.8nm layers of In0.23Ga0.77As in GaAs shows promising characteristics with regard to the total dipole strength which can be coupled to the field mode.
Journal of Physics: Conference Series
PUBLISHED
Keywords: Condensed matter physics; Semiconductors; Nanoscience & Materials